Efficacy and prognosis of dapagliflozin in the treatment of patients with acute myocardial infarction complicated with type 2 diabetes in Xining area - Chai, Jinping; Li, Delian; Liu, Yanmin; Su, Xiaoling (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe acute myocardial infarction (AMI) is a prevalent and severe cardiovascular disease, characterized by its sudden onset, high mortality rate, and unfavorable prognosis. The presence of type 2 diabetes not only signifies a chronic metabolic disorder, but also serves as a catalyst for various cardiovascular and cerebrovascular ailments such as coronary heart disease and stroke. Xining is situated in a region of middle to high altitude and due to its unique geographical environment, coupled with the population's limited health awareness, unequal medical standards and other factors, there remain some AMI patients who are difficult to diagnose early on. The objective of this study is to investigate the efficacy and prognosis of dapagliflozin in patients with acute myocardial infarction complicated by type 2 diabetes in the Xining region.Methodanalysis on January 1, 2018 to January 1, 2020, in Qinghai province people's hospital of cardiovascular internal medicine hospital treatment of 245 cases of acute myocardial infarction combined the clinical data of patients with type 2 diabetes. The patients were divided into dapagliflozin group and control group according to whether they took dapagliflozin during hospitalization. The basic data, laboratory examination indicators and long-term prognosis of the two groups were observed. Follow-up deadline is December 31, 2023, at the end of follow-up, including the primary endpoint and the secondary endpoint.Results245 patients were included in this study, age 34–94, the average age (61–11), 200 cases (81.63%) of men, women, 45 cases (18.37%), dapagliflozin group of men 92 cases (77.97%) and control group, 108 cases (85.04%). Two groups of patients' age, gender, diabetes duration, merge disease, echocardiogram and blood biochemical indexes, had no statistical difference (P > 0.05). There were no significant differences in the number of coronary artery lesions, treatment regimens, cardiovascular and hypoglycemic drugs between the two groups (P > 0.05). However, up to dapagliflozin group of patients after discharge significantly lower than the control group, the incidence of cardiovascular adverse events at dapagliflozin group of 4 cases of heart failure and cardiovascular death in 1 case and control group in heart failure 13 cases, 10 cases of cardiovascular death, cerebral hemorrhage 2 cases died. KaplanMeier survival analysis showed that the primary endpoint of survival was significantly higher in the dapagliflozin group than in the control group (P < 0.05). In addition, the overall survival rate of the dapagliflozin group was significantly higher than that of the control group, and the difference was statistically significant (P < 0.05).ConclusionsDapagliflozin is safe and reliable in the treatment of patients with acute myocardial infarction and type 2 diabetes, and can effectively reduce the incidence of cardiovascular events and improve the overall survival rate of patients.